Mechanism of transcriptional regulation by the Escherichia coli nitric oxide sensor NorR. (20th January 2006) - Tucker, N.P.; D'Autréaux, B.; Spiro, S.; Dixon, R.
Abstract : Nitric oxide (NO) is a highly reactive water-soluble gas encountered by bacteria endogenously as an intermediate of denitrification and exogenously as one of the radical species deployed by macrophages against invading pathogens. Bacteria therefore require a mechanism to detoxify NO. Escherichia coli flavorubredoxin and its associated oxidoreductase, encoded by the norV and norW genes respectively, reduces NO to nitrous oxide under anaerobic conditions. Transcription of the norVW genes is activated in response to NO by the σ 54 -dependent regulator NorR, a member of the prokaryotic enhancer binding protein family. NorR binds co-operatively to three enhancer sites to regulate transcription of both norVW and the divergently transcribed norR gene. In the present paper, we show that disruption of any one of the three GT-(N7 )-AC NorR binding sites in the norR – norVW intergenic region prevents both activation of norVW expression and autogenous repression of the norR promoter by NorR. We have recently demonstrated that the N-terminal GAF (cGMP-specific and -stimulated phosphodiesterases, Anabaena adenylate cyclases and Escherichia coli FhlA) domain of NorR contains a non-haem mononuclear iron centre and senses NO by formation of a mono-nitrosyl iron complex. Site-directed mutagenesis has identified candidate protein ligands to the ferrous iron centre in the GAF domain.